The place of nasolabial flap in orofacial reconstruction: A review - Rahpeyma, Amin (Ann Med Surg (Lond), 2016)
BACKGROUND: The use of Nasolabial flap (NLF) to reconstruct orofacial soft tissue defects is one of the oldest methods for reconstruction in the medical literature. Despite widespread use of this invaluable flap, there are still controversies over the terms used for the description of this flap. MATERIALS AND METHODS: A search was run in PubMed for articles in English language on nasolabial flap in oral cavity/facial reconstruction, between 1960 and 2016. Inclusion criteria was case series that focused on the anatomy, flap design, blood supply, composition, flap motion, and the reconstructed area and donor site complications. RESULTS: 560 articles were found in PubMed search for nasolabial flap (between 1960 and 2016). 84 articles with case series structure and available full text were included. The results of the search in this topic for anatomy, flap design, blood supply,NLF composition, flap motion, reconstructed area and donor site morbidity are presented. CONCLUSION: Nasolabial flap is an old flap for reconstructive purposes. Over time different modifications have been introduced to expand its usage. Clear definition of the terms used with this flap is given.